Did domestic travel restrictions slow down the COVID-19 pandemic in Saudi Arabia? A joinpoint regression analysis - Sami Ajbar; Mohammad Asif; Abdelhamid Mohamed Ajbar (Inishmore Laser Scientific Publishing Ltd, 2021)
# Background Saudi Arabia has recorded the largest number of COVID-19 cases in the Arab world. However, since September 2020 the number of cases has been falling steadily. Various factors may have been behind this success. Joinpoint software is a freely available program that allows the detection of statistically significant trends in data. This paper uses this tool to explore specifically the impact of domestic travel restrictions on the control of the pandemic. # Methods Data for COVID-19 cases were collected from 2 March 2020 until the first of August 2020. Data analysis was done for the country and four cities. Public perception of the severity of the pandemic was included by fitting time-dependent case fatality rate (CFR). The analysis detected joinpoints that were compared with key dates during which travel restrictions were imposed or relaxed. # Results Data analysis revealed that most changes in COVID-19 cases in the country and the selected cities could not be linked to travel restrictions, except for the partial lifting of curfew on 21 April to accommodate the fasting month of Ramadan and the lifting of domestic travel restrictions around 28 May which contributed to a surge in cases. Moreover, time changes of CFR for the whole country did not coincide with any intervention measures' dates other than 28 May # Conclusions While the analysis was able to link some changes in COVID-19 cases to travel restrictions, it was unable to relate sudden surges or declines in the number of disease cases to any intervention measures. Given the difference in population size of the studied cities, their different geographical location, the fact they have been subjected to travel restrictions at different times and of different severity, and given that public perception of the pandemic was included in the analysis, we can conclude with confidence that either COVID-19 data were under-collected as a large segment of population was not tested and/or that domestic travel restrictions played only a limited role compared to other measures such as compulsory wearing of masks, public sector lockdown and schools closing.